Epigallocatechin-3-gallate: A phytochemical as a promising drug candidate for the treatment of Parkinson’s disease - Wang, Yumin; Wu, Shuang; Li, Qiang; Lang, Weihong; Li, Wenjing; Jiang, Xiaodong; Wan, Zhirong; Chen, Jichao; Wang, Hongquan (Frontiers in Pharmacology, 2022)
Epigallocatechin 3-gallate (EGCG), an abundant polyphenolic component derived from green tea extract, possesses versatile bioactivities that can combat many diseases. During the last decade, EGCG was shown to be effective in experimental models of Parkinson’s disease (PD). Several experimental studies have suggested that it has pleiotropic neuroprotective effects, which has enhanced the appeal of EGCG as a therapeutic strategy in PD. In this review, we compiled recent updates and knowledge of the molecular mechanisms underlying the neuroprotective effects of EGCG in PD. We focused on the effects of EGCG on apoptosis, oxidative stress, inflammation, ferroptosis, modulation of dopamine production, and the aggregation of α-synuclein. The review highlights the pharmacological features of EGCG and its therapeutic implications in PD. Taken together, the accumulated data indicate that EGCG is a promising neuroprotective compound for the treatment of PD.